Boundaries of text in the works of conceptual artist Mary Kelly - Žužul, Ivana; Martinović, Barbara (Poznańskie Studia Slawistyczne, 2025)
The paper analyses boundaries between image, text, and context and their transgressions in Mary Kelly’s artworks Post-Partum Document (1973–1979) and Interim (1984–1989). Both hold a significant place in the canon of feminist visual art, and both are predominantly textually based. Authors such as Norman Bryson and Laura Mulvey therefore often indicated the importance of narrativity in Kelly’s artworks. Our research approaches Kelly’s art from multiple interpretative perspectives such as postclassical narratology, feminist literary criticism and theory, and visual studies. The interpretation of the installations examines the consequences of the discursive presence of women in a cultural-theoretical and artistic context.